Antibacterial Activity Test of Ethanol, N-Hexane, and Ethyl Acetate Extracts of Lemon Peel (Citrus x limon (L.) Burm. f.) - Nisa, Uswatun; Mambang, D Elysa Putri; Yuniarti, Rafita; Ridwanto, Ridwanto (Indonesian Journal of Science and Pharmacy, 2025)
Staphylococcus hominis and Pseudomonas aeruginosa bacteria are normal flora bacteria found on the surface of human skin, and in certain circumstances can cause infections in the body of a person with a weak immune system. Infection of both bacteria can cause body odor that can affect a person's social relationships. The use of natural antibacterials has minimal side effects, namely lemon peel which is waste from lemons. Lemon juice is commonly used by the public, but not many people know that lemon peel has great benefits like lemon juice. The objective of the research was to determine the chemical compounds contained in the n-hexane fraction, ethyl acetate of lemon peel and antibacterial activity in ethanol extract, n-hexane fraction, ethyl acetate of lemon peel (Citrus x limon (L.) Burm. f.) This research method was an experimental method that includes sample collection and processing, characterization of simple drugs, preparation of 96% ethanol extract, n-hexane fraction, ethyl acetate fraction, phytochemical screening, and antibacterial activity test using the agar diffusion method at concentrations of 10%, 20%, 30%, 40%, 50%. The results of phytochemical screening in the ethyl acetate fraction contain alkaloids, flavonoids, tannins, triterpenoids, and in the n-hexane fraction shows the presence of triterpenoid chemical compounds. Ethanol extract, n-hexane fraction and ethyl acetate fraction of lemon peel have antibacterial activity on Staphylococcus hominis and Pseudomonas aeruginosa bacteria. The results of the three samples tested for the greatest inhibitory power in the ethyl acetate fraction showed intermediate results, almost comparable to the inhibitory power of the positive control ciprofloxacin.